Key takeaways from the Asia Pacific Medical Education Conference (APMEC) 2025 - Shuh Shing Lee; Jillian Han Ting Yeo; Dujeepa D Samarasekera (The Asia Pacific Scholar)
Introduction: The Asia Pacific Medical Education Conference (APMEC) 2025 focused on evolving medical education amidst global transformations. The theme, "Developing a Holistic Healthcare Practitioner for a Sustainable Future," emphasised integrating sustainability, inclusivity, and advanced technologies like AI into healthcare education. Methods: APMEC 2025 featured a comprehensive program including 29 workshops, 1 special course, 2 keynote speeches, 6 plenary sessions, 19 symposia, and 3 panel discussions, with 84 free communications and 107 short communications presented. The conference facilitated dialogues on innovative curriculum design, sustainability in healthcare education, AI integration, and interprofessional education. Results: Key discussions emphasised incorporating "Possibility Thinking" and student-centered learning, embedding planetary health in curricula, and integrating AI while preserving essential human skills like empathy. The NUS Common Curriculum for Healthcare Professional Education demonstrated significant improvements in empathy and teamwork. The conference highlighted the importance of faculty development and inclusivity, particularly concerning disability in medical education. Conclusion: APMEC 2025 demonstrated a commitment to transforming medical education through collaboration and innovation. By aligning educational practices with global trends and regional needs, APMEC serves as a catalyst for comprehensive curriculum reforms. Ongoing efforts are needed to translate these insights into actionable strategies, ensuring future healthcare professionals are well-prepared to address dynamic global challenges.